2021
DOI: 10.1128/msphere.00549-21
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis PE_PGRS20 and PE_PGRS47 Proteins Inhibit Autophagy by Interaction with Rab1A

Abstract: Tuberculosis is a significant global infectious disease caused by infection of the lungs with Mycobacterium tuberculosis , which then resides and replicates mainly within host phagocytic cells. Autophagy is a complex host cellular process that helps control intracellular infections and enhance innate and adaptive immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 63 publications
(109 reference statements)
0
24
0
Order By: Relevance
“… 2016 ; Strong et al . 2021 ). Under basal autophagy conditions, PE_PGRS47-deficient H37Rv was susceptible to autophagy-mediated elimination, resulting in enhanced autophagy-mediated MHC-II antigen presentation (Saini et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2016 ; Strong et al . 2021 ). Under basal autophagy conditions, PE_PGRS47-deficient H37Rv was susceptible to autophagy-mediated elimination, resulting in enhanced autophagy-mediated MHC-II antigen presentation (Saini et al .…”
Section: Discussionmentioning
confidence: 99%
“… 2016 ; Strong et al . 2021 ). However, the dampening effect of PE_PGRS47 on the autophagy-mediated MHC-II antigen presentation mentioned above was eliminated when autophagy was induced by rapamycin treatment of host cells (Saini et al .…”
Section: Discussionmentioning
confidence: 99%
“…To confirm our previous findings using a transposon mutant with a mutation in the ppe51 gene ( 30 ), we used Δ 51 to assay autophagy and bacterial survival in macrophages. Autophagy was increased in the RAW 264.7 macrophage cell line infected with Δ 51 compared to WT or Δ 51 C infection ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Alternatively to canonical autophagy inhibition, PknG induces canonical autophagy but inhibits autophagy flux by targeting Rab14 ( 29 ). Our recent studies also demonstrated that PE_PGRS20 and PE_PGRS47 inhibit autophagy in macrophages via association with Rab1A ( 30 ).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation